Less conservative conditions for stabilization of switched TS fuzzy systems using fuzzy Lyapunov functions - Faria, Flavio A. [UNESP] (2018)
Relaxed conditions to stabilize switched TS fuzzy systems are proposed. The method considers the addition of slack matrix variables to decrease the conservatism of LMI-based stability conditions. The proposed method is an extension of recent published results. Numerical examples illustrate its efficiency.